2021
DOI: 10.1038/s41419-021-03594-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel lncRNA TCLlnc1 promotes peripheral T cell lymphoma progression through acting as a modular scaffold of HNRNPD and YBX1 complexes

Abstract: Long noncoding RNAs (lncRNAs) play an essential role in tumor progression. Few researches focused on the clinical and biological relevance of lncRNAs in peripheral T cell lymphoma (PTCL). In this research, a novel lncRNA (ENST00000503502) was identified overexpressed in the main subtypes of PTCL, and designated as T cell lymphoma-associated lncRNA1 (TCLlnc1). Serum TCLlnc1 was associated with extranodal involvement, high-risk International Prognostic Index, and poor prognosis of the patients. Both in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Additionally, HIF1A-AS1 recruits pYB-1 to the mRNA of HIF1α , promoting its translation, facilitating glycolysis and enhancing the resistance of pancreatic cancer cells to gemcitabine (a nucleoside antimetabolite) [ 128 ]. Likewise, lncRNAs that interact with YB-1 have been successively identified in liver cancer [ 129 ], gastric cancer [ 130 ], lymphoma [ 131 ], nasopharyngeal cancer [ 132 ], esophageal squamous cell carcinoma [ 133 ], melanoma [ 134 ], and clear cell renal cell carcinoma [ 135 ]. In addition, lncRNA PVT1 indirectly promotes YB-1 expression by sponging miR-216a-5p in colorectal cancer [ 136 ].…”
Section: Upstream Regulation Of Yb-1mentioning
confidence: 99%
“…Additionally, HIF1A-AS1 recruits pYB-1 to the mRNA of HIF1α , promoting its translation, facilitating glycolysis and enhancing the resistance of pancreatic cancer cells to gemcitabine (a nucleoside antimetabolite) [ 128 ]. Likewise, lncRNAs that interact with YB-1 have been successively identified in liver cancer [ 129 ], gastric cancer [ 130 ], lymphoma [ 131 ], nasopharyngeal cancer [ 132 ], esophageal squamous cell carcinoma [ 133 ], melanoma [ 134 ], and clear cell renal cell carcinoma [ 135 ]. In addition, lncRNA PVT1 indirectly promotes YB-1 expression by sponging miR-216a-5p in colorectal cancer [ 136 ].…”
Section: Upstream Regulation Of Yb-1mentioning
confidence: 99%
“…We showed that the increased TCLlnc1 in plasma is correlated with distant metastasis of gastric cancer and may serve as a potential biomarker to diagnose gastric cancer and predict the survival of gastric cancer patients. In a recent study, Zhao et al [17] functionally characterized a novel lncRNA named TCLlnc1 in T cell lymphoma. In T cell lymphoma, TCLlnc1 is significantly overexpressed and it plays a role as the modular scaffold of YBX1 and HNRNPD complexes to promote cancer progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Zhao et al [17] functionally characterized a novel lncRNA named TCLlnc1 in T cell lymphoma. In T cell lymphoma, TCLlnc1 is significantly overexpressed and it plays a role as the modular scaffold of YBX1 and HNRNPD complexes to promote cancer progression [17]. However, the expression pattern of TCLlnc1 in other cancers is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of tens of thousands of metazoan lncRNAs discovered from cDNA libraries and RNAseq data by high throughput transcriptome projects, only a handful of lncRNAs have been functionally characterized. The investigations on this small cohort of lncRNAs have demonstrated that these noncoding transcripts can serve as scaffolds or guides to regulate protein-protein or protein-DNA interactions [28][29][30][31] or can modulate post-translational modification of nonhistone proteins [32]. Moreover, lncRNAs are capable of controlling microRNAs (miRNAs) [33][34][35], and function as enhancers to influence gene transcription, when transcribed from the enhancer regions (enhancer RNA) [36][37][38] or their neighboring loci (noncoding RNA activator) [39,40].…”
Section: Long Non-coding Rna Structures and Functionsmentioning
confidence: 99%